PEMBAHARUAN HUKUM KELUARGA DI ALJAZAIR - Fatimatuz Zahro; Alfiah (Sekolah Tinggi Ilmu Syariah Abu Zairi Bondowoso, 2025)
This article discusses the dynamics of family law reform in Algeria as a reflection of the complex interaction between Islamic tradition, the French colonial legacy, and the demands of modernity. After gaining independence in 1962, Algeria sought to build a national legal system that integrated the principles of Islamic Sharia, particularly the Maliki school, into the Family Law of 1984. Further reforms took place in 2005 in response to demands for gender equality and the protection of women’s rights, which included adjustments to the legal age of marriage, strengthening women’s rights to divorce, and restricting polygamy. The article also highlights the socio-cultural challenges in implementing the law, including resistance from conservative groups, gender inequality, and patriarchal influences. Using a descriptive-analytical approach, the article concludes that although the reforms have brought significant progress in protecting family rights, their implementation still requires structural and cultural support in order to be effectively applied within society. Keywords: Algeria, family law, reform, gender equality, Maliki school